Perioperative Analgesia for Patients Undergoing Thyroidectomy and Parathyroidectomy: An Evidence-Based Review. (October 2020) - Nguyen, Brandon K.; Stathakios, James; Quan, Daniel; Pinto, Jessica; Lin, Hosheng; Pashkova, Anna A.; Svider, Peter F.
Objective: To perform an evidence-based systematic review evaluating perioperative analgesia, including opioid alternatives, used for patients undergoing thyroidectomy and parathyroidectomy. Methods: A comprehensive literature search from 1997 to January 2018 of Pubmed, Cochrane, and EmBase libraries was performed for studies reporting analgesic administration following thyroid or parathyroid surgery. This systematic review was based on the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Studies were evaluated for level of evidence and given a Jadad score to assess for risk of bias. Outcomes gathered included postoperative pain scores, time to rescue analgesia, rescue analgesic consumption, and adverse events. Results: Thirty-eight randomized controlled trials met inclusion criteria. The GRADE criteria determined the overall evidence to be moderate-high. Studies utilizing NSAIDs reported reduced requirements for rescue analgesics. Acetaminophen studies presented with conflicting data on effectiveness. Gabapentinoid studies demonstrated lower pain scores and an increased time to rescue analgesic. Local anesthetics were effective at decreasing Visual Analogue Scale (VAS) and Numeric Rating Scale (NRS) pain scores while also reducing rescue analgesic consumption. Ketamine was shown to increased postoperative nausea and vomiting. NSAIDs and local anesthetic studies had an aggregate grade of evidence A, while all others had grade B evidence. Conclusion: There is significant evidence supporting the use of NSAIDs and local anesthetics in the perioperative period for pain management for thyroid and parathyroid surgeries. Acetaminophen, gabapentinoid and ketamine have some supporting evidence and may serve as adequate alternatives. Further multi-institutional RCTs are warranted to delineate optimal analgesic regimens. Level of Evidence: NA